Studies on Zero-cost algae based phytoremediation of dye and heavy metal from simulated wastewater - Singh A.; Pal D.B.; Kumar S.; Srivastva N.; Syed A.; Elgorban A.M.; Singh R.; Gupta V.K. (My University, 2025)
In the present study, filamentous algae, an emerging candidate for biofuel and other useful chemical production, has been investigated as a biological adsorbent for the removal of contaminants from synthetic wastewater. Operational parameters were optimized in batch phytoremediation experiments. The adsorption equilibrium isotherm models such as Langmuir, Freundlich, and Dubinin-Radushkevitch and kinetics models such as pseudo-1st and pseudo-2nd order in methylene blue decolorization and Cr(VI) removal were also investigated. The D-R isotherm theory provided the best fit. The pseudo-2nd order model accurately described the adsorption kinetic data. Maximum adsorption capacities were observed to 5.03 mg.g−1 and 0.77 mg.g−1 along with removal efficiencies were achieved to 91.3% and 91.4% for methylene blue and Cr(VI) remediation, respectively. Moreover, intra-particle diffusion kinetic theory was used to describe the mechanism. These outcomes are significant in the development of algae-based zero-cost pollutants removal technology in wastewater treatment. © 2021 Elsevier Ltd